Disentangling Large- and Small-Scale Abiotic and Biotic Factors Shaping Soil Microbial Communities in an Alpine Cushion Plant System - Chenyue Wang; Richard Michalet; Ziyang Liu; Xingpei Jiang; Xiangtai Wang; Gaosen Zhang; Gaosen Zhang; Lizhe An; Shuyan Chen; Sa Xiao (Frontiers in Microbiology, 2020)
Microorganisms play a crucial role in biogeochemical cycles and ecosystem processes, but the key factors driving microbial community structure are poorly understood, particularly in alpine environments. In this study, we aim to disentangle the relative contribution of abiotic and biotic factors shaping bacterial and fungal community structure at large and small spatial and integration scales in an alpine system dominated by a stress-tolerant cushion species Thylacospermum ceaspitosum. These effects were assessed in two mountain ranges of northwest China and for two contrasting phenotypes of the cushion species inhabiting two different microtopographic positions. The large- and small-scale abiotic effects include the site and microhabitat effects, respectively, while the large- and small-scale biotic effects include the effects of cushion presence and cushion phenotype, respectively. Soil microbial communities were characterized by Illumina Miseq sequencing. Uni- and multivariate statistics were used to test the effects of abiotic and biotic factors at both scales. Results indicated that the site effect representing the soil pH and abiotic hydrothermal conditions mainly affected bacterial community structure, whereas fungal community structure was mainly affected by biotic factors with an equal contribution of cushion presence and cushion phenotype effects. Future studies should analyze the direct factors contributing to shaping microbial community structure in particular of the cushion phenotypes.